A quantitative approach in mine water balances and strategic management - Mostert, Joseph Ferdinand Willem (University of the Free State, 2014)
The vital role of water within the mining industry, both as an asset which generates value as well as a shared natural resource requiring responsible stewardship, have long been recognised. Due to extreme climate changes, an increasing population density and poor water management, securing of water has become a global challenge and water scarcity will continue to be one of the greatest challenges facing mine water management. There is no simple recipe for mine water management and regulations by environmental authorities, along with past polluting practices, are forcing mining operations to improve and prioritise their water consumption. Accordingly, this sector is expected to be increasingly required to demonstrate leadership through innovative water use management. A mine water balance is considered to be one of the most important and fundamental tools available for mining operations as management begins with a basic understanding of where water is sourced from, and where it is utilised. With this kept in mind, a mine water balance should be based on a holistic systems model approach with an appropriate relationship between the required level of complexity in the model structure and purpose. Excessive detail can cause the model to become clumsy and tend not to focus on strategic water management principles. Emphasis should be put on a system approach, taking into consideration the main interactions, feedbacks and functional relationships between the various parts of the whole system. An overall mine water balance that superimposes different water systems can be divided into a process water system and a natural water system. The natural water system is associated with the intrinsic hydrological cycle and is often disregarded due to uncertainties. It can however significantly impact on mine water usage and losses as indicated in this case study. Consequently, decision making and management options should be based on the evaluation of the system as a whole and inclusion of the natural system as a component of the mine water balance is imperative for accurate quantification. The natural system includes a surface water environmental circuit as well as a groundwater environmental circuit. Surface and groundwater resources have historically been managed separately, but more than ever before, interaction between these two systems are required to facilitate effective resource management. Mining activities have a major effect on the modification of the hydrological regime and the influence of increased hydraulic conductivity along with mining induced recharge, should be evaluated as part of the adapted mine water balance. Furthermore, mine dewatering predictions and climatic scenarios must be incorporated to reflect site conditions more accurately. As poor water management poses an operational risk to mining operations, this sector has developed novel ways to respond to water issues in differing circumstances and has illustrated the ability to turn risk into opportunity. Now, more than ever, special measures are needed to identify options for life-of-mine strategies and initiatives for water conservation and management. Future focus should be to continue investigation and implementation of the water use strategies in order to improve performance across operations and encourage engagement with other water users. Moreover, to share experiences, learn from others and contribute to water discussions and debate at local, national and international levels.

Die wesenlike rol van water in die mynbedryf, as ‘n aanwins wat waarde kan toevoeg, asook as ‘n natuurlike hulpbron wat verantwoordelike rentmeesterskap verg, word reeds jare lank erken. Ekstreme klimaatstoestande, ‘n toenemende bevolkingsdigtheid asook wanbestuur van water, is alles faktore wat water sekuriteit beïnvloed en is besig om in ‘n internasionale krisis te ontaard. Gevolglik word die beskikbaarheid van water beskou as een van die bedryf se grootste uitdagings tot op hede. Daar is nie ‘n eenvoudige oplossing vir myn-water bestuur nie en regulasies deur omgewingsdepartemente, asook historiese besoedelings praktyke forseer mynbedrywighede om water gebruik te optimiseer en te prioritiseer. Daar word voorspel dat die mynbedryf in ‘n toenemende mate geverg gaan word om leierskap te openbaar deur middel van inoverende bestuur. ‘n Waterbalans word beskou as een van die belangrikste en mees fundamentele instrumente beskikbaar vir mynbedrywighede en word geskoei op die basiese begrippe van waar water verkry word, asook waar water verbruik word. Gevolglik moet ‘n myn-waterbalans gebaseer word op ‘n holistiese, sistemiese model-benadering met ‘n toepaslike verhouding tussen die kompleksiteit van die model en die doel van die model. Oorbodige detail kan ’n oneffektiewe en lomp model tot gevolg hê wat geneig is om nie te fokus op strategiese bestuur van water nie. ‘n Sistemiese benadering moet beklemtoon word en interaksies en funksionele verwantskappe tussen eenhede van die stelsel as ‘n geheel, moet in aggeneem word. ‘n Algehele myn-waterbalans is oorliggend aan twee water sisteme naamlik, ‘n proses water sisteem, asook ‘n natuurlike water sisteem. Water van die natuurlike sisteem word geassosieër met die intrinsieke hidrologiese siklus en word dikwels afgeskeep as gevolg van onseker veranderlikes. Dit kan tog steeds ‘n noemenswaardige impak hê op water verbruik en verliese by mynbedrywighede, soos gedemonstreer in die gevalle studie. Besluitneming en bestuursopsies moet ge-evalueer word op grond van ‘n sistemiese benadering en die insluiting van die natuurlike sisteem as ‘n komponent van die myn-waterbalans is uiters noodsaaklik vir akkurate kwantifisering en voorspelling van kondisies op die myn. Water van die natuurlike sisteem kan opgedeel word in opervlak - asook grondwater siklusse. Histories is oppervlak- en grondwaterbronne afsonderlik bestuur, maar interaksie tussen die twee sisteme word benodig om effektiewe hulpbronbestuur en behoorlike besluitneming te bewerkstellig. Gevolglik moet die konvensionele waterbalans aangepas word om voorsiening te maak vir die insluiting van water van die natuurlike siteem. Myn-aktiwiteite het ‘n wesenlike effek op die modifikasie en verandering van die hidrologiese stelsel en, na aanleiding hiervan, moet die invloed van ‘n verhoogde hidrologiese kondutiwiteit, tesame met vermeerdering in grondwater aanvulling, ondersoek word as deel van die gemodifiseerde myn-waterbalans. Verder moet voorspelling van myn-ontwaterings volumes asook verskillende klimaats-alternatiewe in die myn-waterbalans geïnkorporeer word. Sodoende sal ‘n meer verteenwoordigende weerspieëling vir terrein kondisies verkry word. Swak bestuur van water op mynbedrywighede hou ‘n operasionele risiko in en hierdie sektor het gevolglik met innoverende oplossings vorendag gekom om sulke situasies in geleenthede te omskep. Spesiale afmetings en metodes om inisiatiewe te identifiseer vir die bewaring en strategiese bestuur van water, word al hoe meer benodig. Toekomstige fokus moet geplaas word op die bestudering en implementering van strategieë wat operasionele effektiwiteit sal verbeter, asook inskakeling met mede-water verbruikers. Ervaring ten opsigte van hierdie aspek moet gedeel word om sodoende ‘n bydrae te lewer word op ’n plaaslike, maar ook nasionale en internasionale vlak.
Dissertation (M.Sc. (Institute for Groundwater Studies))--University of the Free State, 2014
Keywords: Mine water; Mineral industries; Mine water -- Environmental aspects; Water quality management